Distribution and Use of Income from Bushmeat in a Rural Village, Central Gabon - Coad, L.M.; Abernethy, K.A.; Balmford, A.; Manica, A.; Airey, L.; Milner-Gulland, E.J. (Wiley, 2010)
Abstract:  Bushmeat hunting is an activity integral to rural forest communities that provides a high proportion of household incomes and protein requirements. An improved understanding of the relationship between bushmeat hunting and household wealth is vital to assess the potential effects of future policy interventions to regulate an increasingly unsustainable bushmeat trade. We investigated the relationship between hunting offtake and household wealth, gender differences in spending patterns, and the use of hunting incomes in two rural forest communities, Central Gabon, from 2003 to 2005. Households in which members hunted (hunting households) were significantly wealthier than households in which no one hunted (nonhunting households), but within hunting households offtakes were not correlated with household wealth. This suggests there are access barriers to becoming a hunter and that hunting offtakes may not be the main driver of wealth accumulation. Over half of the money spent by men in the village shop was on alcohol and cigarettes, and the amount and proportion of income spent on these items increased substantially with increases in individual hunting offtake. By contrast, the majority of purchases made by women were of food, but their food purchases decreased actually and proportionally with increased household hunting offtake. This suggests that the availability of bushmeat as a food source decreases spending on food, whereas hunting income may be spent in part on items that do not contribute significantly to household food security. Conservation interventions that aim to reduce the commercial bushmeat trade need to account for likely shifts in individual spending that may ensue and the secondary effects on household economies.